Assessing the cost of electronic health records: a review of cost indicators. (2010)
We systematically reviewed PubMed and EBSCO business, looking for cost indicators of electronic health record (EHR) implementations and their associated benefit indicators. We provide a set of the most common cost and benefit (CB) indicators used in the EHR literature, as well as an overall estimate of the CB related to EHR implementation. Overall, CB evaluation of EHR implementation showed a rapid capital-recovering process. On average, the annual benefits were 76.5% of the first-year costs and 308.6% of the annual costs. However, the initial investments were not recovered in a few studied implementations. Distinctions in reporting fixed and variable costs are suggested.